Trend Bisnis Digital UMKM Sate Madura Cak Ardi: Analisis Strategi Promosi dalam Perkembangan Kewirausahaan Pendampingan di Kota Malang - Moh. Hefni Munawar; Agus Hermawan; Agung Winarno (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2026)
The acceleration of digitalization has created both opportunities and challenges for micro, small, and medium enterprises (MSMEs), particularly traditional culinary businesses that face intense market competition and changing consumer behavior. Many MSMEs still experience limitations in digital literacy and promotional management, which hinder their business growth and sustainability. This study aims to analyze digital business trends and examine digital promotional strategies implemented by UMKM Sate Madura Cak Ardi in supporting entrepreneurial development through business assistance in Malang City. The research employed a qualitative descriptive approach using participatory methods. Data were collected through in-depth interviews, direct observation, and documentation during the mentoring process. The findings show that the adoption of digital platforms, including social media marketing, online food delivery services, digital payment systems, and Google Business Profile, significantly improved business visibility, customer engagement, and operational efficiency. Promotional strategies such as content-based marketing, visual branding, customer reviews, and promotional campaigns proved effective in strengthening brand identity and expanding market reach. Moreover, entrepreneurial mentoring enhanced the owner’s managerial capabilities and adaptability to digital market dynamics. This study concludes that the integration of digital promotional strategies supported by structured business assistance plays a vital role in strengthening the competitiveness and sustainability of traditional MSMEs in the digital era.